Brass bar for hot forging and preparation method thereof

By optimizing the components and microstructure of brass rods, controlling the hardness difference and hard grain points, improving metal flowability and uniformity, the mold wear problem is solved and the service life of hot forged molds is improved.

CN117051284BActive Publication Date: 2025-09-05JINTIAN COPPER GROUP CORP NINGBO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310964489.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-09-05
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

The existing brass rods have severe wear in the hot forging process, which affects the service life of the mold. The existing improvements are mainly focused on the mold materials and processes, while ignoring the quality of the hot forging blank.

Method used

By controlling the component proportion and microstructure of the brass rod, especially adding an appropriate amount of Al elements and controlling the difference in surface hardness and core hardness, the difference in metal flow velocity is reduced, friction is reduced, and metal flow and uniformity are improved by controlling the hard particles and grain size. The extruded blank uniform annealing process is adopted to avoid uneven hardness caused by traditional drawing processes.

Benefits of technology

It significantly improves the service life of hot forged molds from 50,000 to 20,000 to 80,000 to 120,000 to 120,000 to 1,000 to 1,000 to 1,000 to 1,000 to 1,000 to 1,000 to 1,000 to 1,000 to 1,000 to 1,000 to

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117051284B_ABST
    Figure CN117051284B_ABST
Patent Text Reader

Abstract

The present invention discloses a brass bar for hot forging, wherein the mass percentages of the components of the brass bar are: Cu: 57-63wt%, Pb≤3.0wt%, Al: 0.03-0.8wt%, P: 0.001-0.008wt%, and the remainder is impurities and Zn; the difference between the surface hardness and the core hardness of the brass bar is in the range of 5-5HB. The use of the brass bar can make the hot forging die have a longer service life. The present invention also discloses a preparation method of the brass bar for hot forging. The process flow of the preparation method of the brass bar for hot forging includes: smelting → horizontal continuous casting → extrusion → homogenization annealing. The brass bar obtained by the preparation method can increase the die life to 80,000-120,000 (hot forging products) / pair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and particularly relates to a brass bar for hot forging and a preparation method thereof. Background Art

[0002] Brass is an alloy composed of copper and zinc. Its room-temperature microstructure changes with the zinc content. According to the Cu-Zn binary phase diagram, brass has three room-temperature microstructures: brass with a zinc content below 35% has a room-temperature microstructure consisting solely of the α phase; brass with a zinc content between 36% and 46% has a room-temperature microstructure composed of both α and β phases, known as duplex brass. Because the β phase exhibits far greater high-temperature plasticity than the α phase, duplex brass exhibits superior hot forging properties compared to single-phase brass.

[0003] Faucets and valves widely used in the plumbing and sanitary ware industries are made from brass through hot forging and CNC machine cutting. Hot forging involves forging above the metal's recrystallization temperature. Hot forging dies are consumable parts, and die costs account for 15-20% of the production cost. Therefore, die life is a key metric of concern in the forging industry. A die's lifespan refers to the number of parts produced from the time it is put into use until it fails due to normal wear and tear. Hot forging dies are subject to both mechanical and thermal loads. On the one hand, the billet generates impact stress on the die surface, while on the other hand, the high-speed flow of the billet and its scale creates intense friction against the die surface. Mechanical loads primarily involve impact and friction, while thermal loads primarily involve alternating heating and cooling. The main failure modes of hot forging dies include wear, cracking, and deformation. Premature die failure not only halts production but also increases costs.

[0004] Among the various major forms of mold failure, wear accounts for approximately 68% of the occurrence rate, cracking accounts for approximately 24%, plastic deformation accounts for approximately 3%, and thermal cracking accounts for approximately 2%. Therefore, wear is the most important factor contributing to mold failure. Wear is complex. During the relative motion between the mold and the blank, wear does not occur in just one form; rather, it often coexists in multiple forms, each intertwined with the other. Wear forms can be categorized as fatigue wear, erosion wear, abrasive wear, and adhesive wear. Fatigue wear is the shedding of metal from the mold surface due to mechanical and thermal stresses during relative motion between the mold surface and the deformed metal surface. Erosion wear is the phenomenon of tiny particles falling onto the mold surface at high speed, repeatedly impacting the surface, causing localized material loss and forming pits and dents. Abrasive wear occurs when hard particles, trapped between the contact surface of the blank and the mold, scrape the mold surface, causing material to detach from the mold surface. Adhesion wear is the transfer or detachment of material from the mold surface during relative motion between the blank and the mold surface. These wear forms are closely related to the hot forging performance of the blank.

[0005] There are many factors that affect the life of the mold. People tend to focus on the metallurgical quality of the mold material, mold design and manufacturing process, forging process, mold lubrication process, and whether the operation is standardized. Few people improve the quality of the hot forging billet itself to increase the service life of the mold.

[0006] The brass rods used for hot forging in the current plumbing and sanitary ware industry are in urgent need of improvement. It is urgent to develop a brass rod with excellent hot forging performance to solve the shortcomings of existing materials and increase the service life of hot forging dies. Summary of the Invention

[0007] The invention provides a brass bar for hot forging. Using the brass bar can ensure that a hot forging die has a longer service life.

[0008] A specific embodiment of the present invention provides a brass bar for hot forging, wherein the mass percentages of the components of the brass bar are: Cu: 57-63wt%, Pb≤3.0wt%, Al: 0.03-0.8wt%, P: 0.001-0.008wt%, and the balance is impurities and Zn;

[0009] The difference between the surface hardness and the core hardness of the brass rod is in the range of -5 to 5 HB.

[0010] The difference between the surface hardness and the core hardness of the brass bar provided by the present invention ranges from -5 to 5 HB. This is because when the difference between the surface hardness and the core hardness of a brass bar is large, the lower-hardness areas have less resistance to hot forging deformation than the higher-hardness areas. As a result, the metal flows faster in the lower-hardness areas, while slower in the higher-hardness areas. The slower-flowing metal, in turn, pulls on the faster-flowing metal, increasing friction between the blank and the die surface and worsening wear on both.

[0011] The content range of each element is controlled based on:

[0012] Cu: When the Cu content is lower than 57wt%, the proportion of brass α phase is too low, and the alloy begins to show brittleness, which leads to stress cracking of hot forged parts during assembly and service. When the Cu content exceeds 63wt%, the room temperature structure of brass gradually changes to a single α phase structure. The α phase has poor high-temperature plasticity, which makes the hot forging performance of brass deteriorate. At the same time, since the Pb content of α phase brass exceeds 0.03wt%, hot brittleness will occur and cracking will occur during hot forging.

[0013] Pb: Pb is not soluble in Cu and is distributed in the form of a single substance within the grain and on the grain boundaries. It can improve the cutting performance of brass. When the Pb content of brass exceeds 3wt%, the cutting performance of brass will not be improved. On the contrary, a large number of Pb particles will gather on the grain boundaries, resulting in a decrease in the strength of the brass.

[0014] Al: Al can increase the proportion of β phase in brass structure, improve the metal fluidity during hot forging of copper rods, and make the metal filling full. When the Al content is lower than 0.03wt%, the effect of improving fluidity is weak. When the Al content exceeds 0.8wt%, Al has a strong solid solution strengthening effect in brass, which leads to an increase in alloy hardness, making brass hot forging blanks difficult to cut during cutting, affecting processing efficiency and reducing tool life.

[0015] P: P in brass can play a deoxidizing role and reduce the oxide inclusions in the copper water; P can also form a ZnO-P2O5 oxide film on the surface of the copper water, which can prevent oxygen in the air from contacting Al in the copper water to form Al2O3 inclusions.

[0016] Furthermore, the brass rod is polished to a thickness of not less than 160 mm. 2 On the polished surface, there are no hard particles larger than 100 μm, and fewer than three hard particles between 30 and 100 μm. This is done to control the presence of hard particles in the blank (i.e., the brass bar) that can cause abrasive wear between the surfaces when in contact with the die. Hard particles smaller than 30 μm are unlikely to cause abrasive wear, and are practically negligible.

[0017] Furthermore, the hard points are one or more of Al2O3, SiO2, Fe3Si, Mn5Si3, Cr-Si, and Mn-Fe-Si.

[0018] Furthermore, the average grain size of the brass bar is controlled within a range of 0.030-0.045 mm. If the grain size is too small, the yield strength is higher, the resistance to hot forging deformation is greater, and the wear on the die is also greater. If the grain size is too large, the tendency to form hot working cracks also increases. The grain size within this range is most conducive to hot forging deformation.

[0019] Furthermore, to control grain uniformity, the area percentage of grains with a grain size of 0.035-0.040 mm is greater than 90%. This is because when grains are uneven, each micro-region of the blank is subjected to different deformation resistances, and the metal fluidity of each micro-region is inconsistent, resulting in mutual restraint, which increases the friction between the blank and the mold surface and exacerbates the wear of the mold surface.

[0020] Furthermore, the brass rod has an α+β phase crystal structure, wherein the β phase accounts for ≥15% of the area at room temperature. When the β phase accounts for ≥15% of the area at room temperature, the β phase accounts for more than 80% of the area at the hot forging temperature of the duplex brass in the range of 600-750°C. Since the high-temperature plasticity of the β phase is far superior to that of the α phase, the metal fluidity reaches an optimal level at the hot forging temperature. The β phase ratio in the duplex brass structure at high temperature is not only related to the heating temperature, but also to the β phase ratio in the brass structure at room temperature. The β phase ratio in the brass structure at room temperature is negatively correlated with the Cu content and positively correlated with the Al content. When the β phase area accounts for less than 15% of the area at room temperature, increasing the hot forging temperature cannot increase the β phase ratio in the duplex brass structure to more than 80%.

[0021] Furthermore, the brass rod for hot forging further comprises As, and the content of As is in the range of 0.01-0.3 wt%.

[0022] As: As is an optional element in the present invention and is added according to the product application. Adding 0.02-0.05wt% of As to brass can prevent dezincification and improve the corrosion resistance of brass. A small amount of As can improve the hot forging performance of brass while having little effect on the mechanical properties. It can also increase the recrystallization temperature of brass and control the grain size.

[0023] Furthermore, the impurities include Fe, Mn, Si, and Cr, wherein the mass percentage of each impurity component in the brass bar is: Fe ≤ 0.2wt%, Mn ≤ 0.1wt%, Si ≤ 0.03wt%, and Cr ≤ 0.05wt%. This is because high levels of impurity elements will form compounds such as Fe2Si3, Mn3Si5, Cr-Si, and Mn-Fe-Si, which will float on the surface of or within the molten copper. If the molten copper does not float to the surface, it will remain in the alloy matrix as hard particles after solidification, thereby wearing out the mold.

[0024] On the other hand, a specific embodiment of the present invention further provides a method for preparing a brass bar for hot forging, comprising:

[0025] S1. According to the percentage of each component of the brass bar for hot forging, raw materials are batched and smelted to obtain molten copper;

[0026] S2, refining the molten copper, comprising:

[0027] S21, adding a slag cleaning agent to the copper solution obtained in step S1, stirring, and then removing the slag;

[0028] S22, adding a refining agent to the molten copper obtained in step S21 to remove high-melting-point oxides generated by oxidation in the molten copper;

[0029] S23, adding CuP14 to the copper solution obtained in step S22 and stirring, wherein the amount of CuP14 added is 0.015-0.08% of the total weight of the copper solution obtained in step S1. The purpose of adding an appropriate amount of CuP14 is to hinder the formation of Al2O3 inclusion hard phase.

[0030] S24. Raise the temperature to 1090-1130℃, spray fire 1-3 times continuously, and let it stand at 1050-1080℃ for 15-30min. The purpose is to remove a large amount of non-metallic inclusions in the copper liquid by the escape of zinc vapor during spraying fire, and to let the non-metallic inclusions such as Al2O3 and SiO2 suspended in the copper liquid float to the surface of the copper liquid by standing, and remove them when slag is removed.

[0031] S25. The copper liquid obtained in step S24 is transferred into an insulated container through a silicon carbide filter plate chute. The silicon carbide filter plate provided by the present invention has a pore size of 20-60 ppi. The silicon carbide filter plate has multiple filtering mechanisms such as interception, filter cake, adsorption, and rectification, which can filter out 0.1-0.5 mm Al2O3, SiO2 and other oxides in the copper liquid to prevent these oxides from forming hard spots in the copper rod.

[0032] S3, horizontally continuously casting the molten copper obtained in step S25 to obtain a master alloy ingot;

[0033] S4. Extrude the master alloy ingot obtained in step S3 at an extrusion temperature of 600-700°C to produce a master alloy rod. If the extrusion temperature is below 600°C, the brass structure of the present invention will contain less β phase and more α phase. The β phase has better high-temperature plasticity than the α phase, resulting in greater resistance to extrusion deformation and difficulty in extrusion. Furthermore, the low extrusion temperature also reduces the dynamic recrystallization temperature, resulting in a recrystallized grain size of less than 30 μm. If the extrusion temperature is above 700°C, the dynamic recrystallization temperature is high, resulting in coarse recrystallized grains in the extruded billet, with a grain size greater than 45 μm. The heated ingot is extruded on a 1250-3150T extruder. The extrusion die should be made of cermet, with specifications calculated based on the extruded billet using the following formula: die diameter = billet diameter * 1.012-1.025. Extrusion ratio: 15-200, extrusion speed: 3-14 mm / s.

[0034] S5. The master alloy bar obtained in step S4 is homogenized and annealed to produce a brass bar for hot forging. The homogenization annealing process is as follows: heating from room temperature to 470-540°C for 30-90 minutes and holding at this temperature for 240-360 minutes. The goal is to eliminate the uneven structure of the extruded billet and obtain a copper bar with uniform grain size and hardness, ensuring that the dominant grains with a grain size of 0.035-0.040 mm account for more than 90% of the total grain area. If the annealing temperature is below 470°C, the dominant grain area ratio will not exceed 90%. If the annealing temperature exceeds 540°C, the average grain size will exceed 45μm, and the dominant grain area ratio will also not reach more than 90%. In addition, hot forging is prone to cracking.

[0035] Furthermore, the raw materials in step S1 are copper, brass recycled material, zinc ingot, lead ingot, aluminum ingot, and copper-phosphorus master alloy, and the order of addition is copper → brass recycled material → zinc ingot → aluminum ingot → lead ingot → copper-phosphorus master alloy. By adding relatively pure raw materials, the presence of more impurities is reduced, thus forming hard spots that are more difficult to remove in subsequent steps.

[0036] Furthermore, the smelting temperature in step S1 is 1020-1140°C.

[0037] Furthermore, after all the raw materials are melted, the temperature is kept at 1070-1130°C.

[0038] Furthermore, the amount of the slag cleaning agent added is 0.03-0.1% of the total weight of the molten copper obtained in step S1.

[0039] Furthermore, in step S21, the stirring time is 1-3 minutes.

[0040] Furthermore, the refining agent comprises 60-80 wt% cryolite and 20-40 wt% potassium chloride, and is added in an amount of 0.05-0.15 wt% of the molten copper obtained in step S1. This is to remove high-melting-point oxides such as Al2O3 and SiO2 from the molten copper, which are oxidized and eventually form hard spots in the copper rod.

[0041] Furthermore, in step S23, the stirring time is 1-3 minutes.

[0042] Furthermore, the horizontal continuous casting process is as follows: casting temperature 1030-1080°C, ingot specification Φ145-254mm, traction time 0.5-6s, traction pitch 1-12mm, pause time 0.1-2s, reverse push time 0.1-2s, reverse pitch 0.2-3.5mm, and retreat time 0.1-3s.

[0043] Furthermore, the method for preparing brass bars for hot forging provided in a specific embodiment of the present invention further includes:

[0044] Pickling: The purpose of pickling is to remove the oxide scale on the surface of the extruded billet. The volume ratio of the pickling solution is: nitric acid: sulfuric acid: water = 1:12:32.

[0045] Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 0.3-2mm / m.

[0046] Cut to length: The bars are cut and flattened on a sawing and flattening machine to the length required by the customer.

[0047] Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of polishing points.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The present invention improves the fluidity of the metal by adding an appropriate content of Al element to ordinary brass and controlling the difference between the surface hardness and the core hardness of the brass bar, and prevents the slow-flowing metal from in turn involving the fast-flowing metal, thereby reducing the friction between the blank and the mold surface and reducing the wear of the mold.

[0050] The present invention improves the metal fluidity during brass hot forging deformation by coordinated control of the appropriate content of the Al element and the area ratio of the β phase and the area ratio of the dominant grains in the microstructure, thereby reducing the adhesive wear of the blank on the die.

[0051] The invention reduces the abrasive wear of the blank on the die by controlling the quantity of relatively large hard particles Al2O3, SiO2, Cr-Si and Mn-Fe-Si in the copper rod.

[0052] By adding a homogenizing annealing process to the extruded blank without drawing, this invention eliminates the phenomenon in which the surface hardness of copper bars produced by the traditional "extrusion-drawing" process is higher than the core hardness. This ensures uniform metal flow during hot forging of brass, reduces friction between the flowing metal and the die surface, reduces wear on both the metal and the die, and increases the life of the hot forging die. The die life is increased from 5,000 to 20,000 pieces per pair to 80,000 to 120,000 pieces (for hot forged products) per pair. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a metallographic photograph of the brass bar for hot forging prepared in Example 1 of the present invention;

[0054] Figure 2 This is a metallographic photograph of the brass bar for hot forging prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0055] The present invention is described in further detail below with reference to the examples.

[0056] The present invention provides 6 embodiments and 2 comparative examples, and the specific compositions are shown in Table 1.

[0057] Example 1

[0058] 1) Melting: According to the required composition of the alloy, add the materials in sequence and melt them. The melting temperature is 1030-1080℃. After all the raw materials are melted and the components are tested to be qualified, the refining steps are as follows:

[0059] The first step is to add 0.06% of the total weight of the copper solution to the slag remover and stir for 2 minutes before removing the slag.

[0060] Step 2: Add 0.1% refining agent based on the total weight of the copper solution and stir for 6 minutes. The refining agent composition is: 80wt% cryolite and 20wt% potassium chloride;

[0061] Step 3: Add 0.05% CuP14 master alloy based on the total weight of the copper solution and stir for 2 minutes;

[0062] Step 4: Raise the furnace temperature to 1080-1090℃ and spray the flame twice continuously;

[0063] Step 5: Let the copper liquid in the smelting furnace stand for 25 minutes;

[0064] Step 6: The molten copper from the smelting furnace is transferred to the induction furnace through a chute equipped with a silicon carbide filter plate for insulation. The converter temperature is 1080-1110°C and the pore size of the silicon carbide filter plate is 30ppi.

[0065] 2) Horizontal continuous casting: casting temperature: 1050-1060℃, ingot specification: Φ195mm, traction time: 2s, traction pitch: 6mm, pause time: 1.2s, reverse push time: 0.8s, reverse pitch: 1.5mm, retreat time: 1.4s.

[0066] 3) Extrusion: Ingot heating temperature: 650°C. The heated ingot is extruded into a straight rod on a 2200T extruder. The extrusion blank specification is Φ26 mm, the extrusion die specification is Φ26*1.019=Φ26.5 mm, the extrusion ratio is 56.25, and the extrusion speed is 8 mm / s.

[0067] 4) Homogenization annealing: annealing temperature: 500℃, heating from room temperature, heating time: 60min, after reaching the set temperature, holding time: 240min. The metallographic structure of the brass bar obtained is as follows Figure 1 As shown, Figure 1Detailed explanation: The large block structure is α phase, the small particles distributed in the grain boundaries of the α phase are β phase, the β phase ratio is 24.3%, the average grain size is 0.037mm, of which the dominant grains with a grain size in the range of 0.035-0.040mm account for 96.5%, and no hard spots are visible.

[0068] 5) Pickling: Volume ratio of pickling solution: nitric acid: sulfuric acid: water = 1:12:32.

[0069] 6) Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 0.5mm / m.

[0070] 7) Fixed length: Fixed length: 3m.

[0071] 8) Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of hard spots after polishing.

[0072] Example 2

[0073] 1) Melting: According to the required composition of the alloy, add the materials in sequence and melt them. The melting temperature is 1040-1090℃. After all the raw materials are melted and the composition is tested to be qualified, the refining steps are as follows:

[0074] The first step is to add 0.05% of the total weight of the copper solution to the slag remover, stir for 1 minute, and then remove the slag;

[0075] Step 2: Add 0.08% refining agent based on the total weight of the copper solution and stir for 5 minutes. The refining agent composition is: 70wt% cryolite and 30wt% potassium chloride;

[0076] Step 3: Add 0.06% CuP14 master alloy based on the total weight of the copper solution and stir for 3 minutes;

[0077] Step 4: Raise the furnace temperature to 1080-1090℃ and spray the flame once;

[0078] Step 5: Let the copper liquid in the smelting furnace stand for 30 minutes;

[0079] Step 6: The molten copper from the smelting furnace is transferred to the induction furnace through a chute equipped with a silicon carbide filter plate for insulation. The converter temperature is 1090-1120℃ and the pore size of the silicon carbide filter plate is 30ppi.

[0080] 2) Horizontal continuous casting: casting temperature: 1055-1070℃, ingot specification: Φ254mm, traction time: 2.4s, traction pitch: 5mm, pause time: 1.5s, reverse push time: 1s, reverse pitch: 1.6mm, retreat time: 1.2s.

[0081] 3) Extrusion: Ingot heating temperature: 630°C. The heated ingot is extruded into a straight rod on a 3150T extruder. The extrusion blank specification is Φ88 mm, the extrusion die specification is Φ88*1.023=Φ90 mm, the extrusion ratio is 8, and the extrusion speed is 4 mm / s.

[0082] 4) Homogenization annealing: annealing temperature: 520 ° C, heating from room temperature, heating time: 90 minutes, after reaching the set temperature, holding time: 300 minutes.

[0083] 5) Pickling: Volume ratio of pickling solution: nitric acid: sulfuric acid: water = 1:12:32.

[0084] 6) Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 1.5mm / m.

[0085] 7) Fixed length: Fixed length: 2m.

[0086] 8) Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of hard spots after polishing.

[0087] Example 3

[0088] 1) Melting: According to the required composition of the alloy, the materials are added and melted in sequence. The melting temperature is 1040-1100℃. After all the raw materials are melted and the components are tested to be qualified, the refining steps are as follows:

[0089] The first step is to add 0.08% of the total weight of the copper solution to the slag remover, stir for 1 minute, and then remove the slag;

[0090] Step 2: Add 0.06% refining agent based on the total weight of the copper solution and stir for 8 minutes. The refining agent composition is: 80wt% cryolite and 20wt% potassium chloride;

[0091] Step 3: Add 0.07% CuP14 master alloy based on the total weight of the copper solution and stir for 3 minutes;

[0092] Step 4: Raise the furnace temperature to 1070-1085℃ and spray the flame three times continuously;

[0093] Step 5: Let the copper liquid in the smelting furnace stand for 23 minutes;

[0094] Step 6: The molten copper from the smelting furnace is transferred to the induction furnace through a chute equipped with a silicon carbide filter plate for insulation. The converter temperature is 1090-1120℃ and the pore size of the silicon carbide filter plate is 30ppi.

[0095] 2) Horizontal continuous casting: casting temperature: 1045-1060℃, ingot specification: Φ145mm, traction time: 1.2s, traction pitch: 8mm, pause time: 0.6s, reverse push time: 0.5s, reverse pitch: 1mm, retreat time: 1s.

[0096] 3) Extrusion: Ingot heating temperature: 600°C. The heated ingot is extruded into a straight rod on a 1250T extruder. The extrusion blank specification is Φ16 mm, the extrusion die specification is Φ16*1.024=Φ16.4 mm, the extrusion ratio is 82, and the extrusion speed is 9 mm / s.

[0097] 4) Homogenization annealing: annealing temperature: 470 ° C, heating from room temperature, heating time: 45 minutes, after reaching the set temperature, holding time: 240 minutes.

[0098] 5) Pickling: Volume ratio of pickling solution: nitric acid: sulfuric acid: water = 1:12:32.

[0099] 6) Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 0.3mm / m.

[0100] 7) Fixed length: Fixed length: 3m.

[0101] 8) Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of hard spots after polishing.

[0102] Example 4

[0103] 1) Melting: According to the required composition of the alloy, add the materials in sequence and melt them. The melting temperature is 1030-1080℃. After all the raw materials are melted and the components are tested to be qualified, the refining steps are as follows:

[0104] The first step is to add 0.11% of the total weight of the copper solution to the slag remover and stir for 3 minutes before removing the slag.

[0105] Step 2: Add 0.12% refining agent based on the total weight of the copper solution and stir for 6 minutes. The refining agent composition is: 70wt% cryolite and 30wt% potassium chloride;

[0106] Step 3: Add 0.07% CuP14 master alloy based on the total weight of the copper solution and stir for 2 minutes;

[0107] Step 4: Raise the furnace temperature to 1080-1090℃ and spray the flame twice continuously;

[0108] Step 5: Let the copper liquid in the smelting furnace stand for 20 minutes;

[0109] Step 6: The molten copper from the smelting furnace is transferred to the induction furnace through a chute equipped with a silicon carbide filter plate for insulation. The converter temperature is 1090-1120℃ and the pore size of the silicon carbide filter plate is 30ppi.

[0110] 2) Horizontal continuous casting: casting temperature: 1035-1055℃, ingot specification: Φ175mm, traction time: 2s, traction pitch: 6mm, pause time: 1.2s, reverse push time: 0.5s, reverse pitch: 1.5mm, retreat time: 1.1.

[0111] 3) Extrusion: Ingot heating temperature: 640°C. The heated ingot is extruded into a straight rod on an 1800T extruder. The extrusion blank specification is Φ20 mm, the extrusion die specification is Φ26*1.02=Φ20.4 mm, the extrusion ratio is 76, and the extrusion speed is 9 mm / s.

[0112] 4) Homogenization annealing: annealing temperature: 490 ° C, heating from room temperature, heating time: 50 minutes, after reaching the set temperature, holding time: 330 minutes.

[0113] 5) Pickling: Volume ratio of pickling solution: nitric acid: sulfuric acid: water = 1:12:32.

[0114] 6) Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 0.35mm / m.

[0115] 7) Fixed length: Fixed length: 2.5m.

[0116] 8) Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of hard spots after polishing.

[0117] Example 5

[0118] 1) Melting: According to the required composition of the alloy, add the materials in sequence and melt them. The melting temperature is 1020-1070℃. After all the raw materials are melted and the composition is tested to be qualified, the refining steps are as follows:

[0119] The first step is to add 0.14% of the total weight of the copper solution to the slag remover, stir for 2 minutes and then remove the slag;

[0120] Step 2: Add 0.12% refining agent based on the total weight of the copper solution and stir for 6 minutes. The refining agent composition is: 70wt% cryolite and 30wt% potassium chloride;

[0121] Step 3: Add 0.07% CuP14 master alloy based on the total weight of the copper solution and stir for 2 minutes;

[0122] Step 4: Raise the furnace temperature to 1060-1070℃ and spray the flame three times continuously;

[0123] Step 5: Let the copper liquid in the smelting furnace stand for 30 minutes;

[0124] Step 6: The molten copper from the smelting furnace is transferred to the induction furnace through a chute equipped with a silicon carbide filter plate for insulation. The converter temperature is 1080-1100℃ and the pore size of the silicon carbide filter plate is 30ppi.

[0125] 2) Horizontal continuous casting: casting temperature: 1040-1060℃, ingot specification: Φ254mm, traction time: 2.8s, traction pitch: 4.5mm, pause time: 1.6s, reverse push time: 1.2s, reverse pitch: 2.0mm, retreat time: 1.4s.

[0126] 3) Extrusion: Ingot heating temperature: 655°C. The heated ingot is extruded into a straight rod on a 3150T extruder. The extrusion blank specification is Φ49 mm, the extrusion die specification is Φ49*1.021=Φ50 mm, the extrusion ratio is 25.8, and the extrusion speed is 5 mm / s.

[0127] 4) Homogenization annealing: annealing temperature: 530 ° C, heating from room temperature, heating time: 60 minutes, after reaching the set temperature, holding time: 270 minutes.

[0128] 5) Pickling: Volume ratio of pickling solution: nitric acid: sulfuric acid: water = 1:12:32.

[0129] 6) Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 1.2mm / m.

[0130] 7) Fixed length: Fixed length: 2m.

[0131] 8) Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of hard spots after polishing.

[0132] Example 6

[0133] 1) Melting: According to the required composition of the alloy, the materials are added and melted in sequence. The melting temperature is 1040-1100℃. After all the raw materials are melted and the components are tested to be qualified, the refining steps are as follows:

[0134] The first step is to add 0.09% of the total weight of the copper solution to the slag remover and stir for 2 minutes before removing the slag.

[0135] Step 2: Add 0.11% refining agent based on the total weight of the copper solution and stir for 10 minutes. The refining agent composition is: 80wt% cryolite and 20wt% potassium chloride;

[0136] Step 3: Add 0.02% CuP14 master alloy based on the total weight of the copper solution and stir for 1 minute;

[0137] Step 4: Raise the furnace temperature to 1090-1100℃ and spray the flame twice continuously;

[0138] Step 5: Let the copper liquid in the smelting furnace stand for 27 minutes;

[0139] Step 6: The molten copper from the smelting furnace is transferred to the induction furnace through a chute equipped with a silicon carbide filter plate for insulation. The converter temperature is 1085-1110℃ and the pore size of the silicon carbide filter plate is 30ppi.

[0140] 2) Horizontal continuous casting: casting temperature: 1050-1065℃, ingot specification: Φ195mm, traction time: 2s, traction pitch: 6mm, pause time: 1.2s, reverse push time: 0.9s, reverse pitch: 1.5mm, retreat time: 1.0s.

[0141] 3) Extrusion: Ingot heating temperature: 690°C. The heated ingot is extruded into a straight rod on a 2200T extruder. The extrusion blank specification is Φ35 mm, the extrusion die specification is Φ35*1.02=Φ35.7 mm, the extrusion ratio is 31, and the extrusion speed is 6 mm / s.

[0142] 4) Homogenization annealing: annealing temperature: 500 ° C, heating from room temperature, heating time: 4560 min, after reaching the set temperature, holding time: 240270 min.

[0143] 5) Pickling: Volume ratio of pickling solution: nitric acid: sulfuric acid: water = 1:12:32.

[0144] 6) Straightening: Straighten on a two-roll straightening machine. After straightening, the straightness of the copper rod reaches 0.9mm / m.

[0145] 7) Fixed length: Fixed length: 2.5m.

[0146] 8) Inspection: Check the copper rod’s dimensional tolerance, core and surface hardness, and the number of hard spots after polishing.

[0147] Comparative Example 1

[0148] This comparative example provides the disclosed The crystal structure of the brass rod is as follows: Figure 2 As shown, Figure 2 Detailed explanation: The large block structure is α phase, and a small amount of black small particles distributed at the α phase grain boundaries are β phase. The proportion of β phase is 12.7%, and the average grain size is 0.020mm. Among them, the dominant grains with a grain size in the range of 0.035-0.040mm account for only 15.2%, and some tiny black spots are hard spots.

[0149] Comparative Example 2

[0150] This comparative example provides the disclosed Rod.

[0151] The bars provided in Comparative Examples 1 and 2 are both produced using a conventional process route, which is: smelting → horizontal continuous casting → extrusion → pickling → drawing → pickling → straightening → sizing → inspection.

[0152] The following tests were performed on the microstructures of the obtained embodiments and comparative examples, and the results are recorded in Table 2, which is described in detail: the β phase ratio of the embodiments at room temperature is above 15%, the grain size is in the range of 0.030-0.045 mm, and the proportion of dominant grains reaches above 90%, indicating that the grain size is uniform, the number of hard points with a size of 100 μm or more is 0, and the number of hard points with a size of 30-100 μm is only 1-2. Although the β phase ratio of comparative example 1 is lower than 15%, due to the small grain size, the proportion of dominant grains is low, only 15.2%, and the number of hard points is large, so the die life is short during hot forging; although the β phase ratio of comparative example 2 reaches 44.6%, due to the small grain size, the proportion of dominant grains is even lower, only 4.6%, and the number of hard points is large, so the die life is short during hot forging.

[0153] The grain size, proportion of different grains, and phase ratio were observed under a Leica DMI8C metallographic microscope and measured using LAMOSMasterx64 metallographic analysis software.

[0154] The hardness and difference between the surface and core of the copper rods of the six examples and two comparative examples were tested. The results are recorded in Table 3. Table 3 is explained in detail. The difference between the core and surface hardness of the copper rods of the examples is very small, with the difference ranging from -5 to 5. The hardness uniformity of various parts of the copper rods is good, and the mold life reaches more than 80,000 pieces per pair. However, the difference between the core and surface hardness of the copper rods of the two comparative examples is large, far exceeding the range of -5 to 5. The hardness uniformity of various parts of the copper rods is poor, and thus the mold life is less than 20,000 pieces per pair.

[0155] Hardness HB: Tested according to GB / T 231.1-2018 "Brinell hardness test of metallic materials - Part 1: Test method".

[0156] Polishing hard point detection: The copper rod surfaces prepared in 6 examples and 2 comparative examples were polished, and the polished surface observation area was 160mm 2 Polishing is carried out according to the process of "100# grinding wheel → 240# grinding wheel → 320# grinding wheel → 600# grinding wheel → hemp wheel → cloth wheel". The cloth wheel needs to be polished with polishing wax to obtain a mirror surface, and then observed under a scanning electron microscope.

[0157] Table 1 Compositions of Examples of the Invention and Comparative Examples (wt%)

[0158]

[0159]

[0160] Table 2 Microstructure of the Examples of the Invention and the Comparative Examples

[0161]

[0162] Table 3 Hardness and difference between the core and surface of copper rods in the embodiments of the present invention and comparative examples, as well as the life of hot forging dies

[0163]

Claims

1. A brass bar for hot forging, characterized in that: The mass percentages of the components of the brass rod are: Cu: 57-63wt%, Pb≤3.0wt%, Al: 0.03-0.8wt%, P: 0.001-0.008wt%, and the balance is impurities and Zn; The difference between the surface hardness and the core hardness of the brass bar is in the range of -5 to 5 HB; The average grain size of the brass rod is controlled at 0.030-0.045 mm; The area percentage of grains with a grain size of 0.035-0.040 mm is greater than 90%.

2. The brass bar for hot forging according to claim 1, characterized in that: The brass bars are 160 mm 2 On the polished surface, the number of hard spots with a size of 100 μm or more is 0, and the number of hard spots with a size of 30-100 μm is less than 3.

3. The brass bar for hot forging according to claim 2, characterized in that: The hard points are one or more of Al2O3, SiO2, Fe3Si, Mn5Si3, Cr-Si, and Mn-Fe-Si.

4. The brass bar for hot forging according to claim 1, characterized in that The brass rod has a crystal structure of α+β phase, wherein the β phase area accounts for ≥15% at room temperature.

5. The brass bar for hot forging according to claim 1, characterized in that: The brass rod further comprises As, and the content of As is in the range of 0.01-0.3 wt %.

6. The brass bar for hot forging according to claim 1, characterized in that The impurities include Fe, Mn, Si and Cr, wherein the mass percentage of each impurity component in the brass rod is: Fe≤0.2wt%, Mn≤0.1wt%, Si≤0.03wt%, Cr≤0.05wt%.

7. A method for preparing a brass bar for hot forging according to any one of claims 1 to 6, characterized in that: include: S1. Mixing raw materials according to the percentages of the components of the brass bar for hot forging according to any one of claims 1 to 6, and smelting to obtain molten copper; S2, refining the molten copper, comprising: S21, adding a slag cleaning agent to the copper solution obtained in step S1, stirring, and then removing the slag; S22, adding a refining agent to the molten copper obtained in step S21 to remove high-melting-point oxides generated by oxidation in the molten copper; S23, adding CuP14 to the copper solution obtained in step S22 and stirring, wherein the amount of CuP14 added is 0.015-0.08% of the total weight of the copper solution obtained in step S1; S24. Raise the temperature to 1090-1130°C, spray fire 1-3 times continuously, and let it stand at 1050-1080°C for 15-30 minutes; S25, transferring the copper liquid obtained in step S24 into a heat preservation container through a silicon carbide filter plate chute, wherein the pore size of the silicon carbide filter plate is 20-60 ppi; S3, horizontally continuously casting the molten copper obtained in step S25 to obtain a master alloy ingot; S4, extruding the master alloy ingot obtained in step S3 at an extrusion temperature to obtain a master alloy rod, wherein the extrusion temperature is 600-700° C.; S5. Perform homogenization annealing on the master alloy bar obtained in step S4 to obtain a brass bar for hot forging. The homogenization annealing process is as follows: heating from room temperature to 470-540° C. for 30-90 minutes and holding time for 240-360 minutes.

8. The method for preparing brass bars for hot forging according to claim 7, characterized in that: In step S1, the raw materials are red copper, brass recycled material, zinc ingot, lead ingot, aluminum ingot and copper-phosphorus master alloy, and the order of adding materials is red copper → brass recycled material → zinc ingot → aluminum ingot → lead ingot → copper-phosphorus master alloy.

Citation Information

Patent Citations

  • Hot-forged copper alloy article

    CN103917674A